(untitled) - Asnash, Liviu (Indianapolis, IN, 2007)
Written by Microsoft’s lead developers of Excel Services, this book shares their insights into the benefits and usage of Excel’s new server technology so that you can solve business problems. You’ll learn what Excel Services is for and how it is used, how to deploy an evaluation copy of the server and effectively administer it, and gain an understanding of how the server works. You’ll also get step-by-step guidelines for using the server in each of the scenarios for which it was designed
Keywords: Microsoft Excel (Computer file),Business,Electronic spreadsheets,Microsoft Excel; Computer programs